Our grateful dead : stories of those left behind - Despret, Vinciane (University of Minnesota Press, 2021)
"Vinciane Despret's unique storytelling, woven with ethnography and family history, assembles accounts of those living their daily lives with their dead"-- Provided by publisher.
Translated from the original French into English.
"Originally published in French as Au bonheur des morts, Récits de ceux qui restent. Copyright Éditions La Découverte, Paris, 2015, 2017."
Keywords: Dead.; Mourning customs.; Grief.; Death -- Social aspects.; Death -- Psychological aspects.; Morts.; Deuil -- Coutumes.; Chagrin.; Mort -- Aspect social.; Mort -- Aspect psychologique.; grief.; SOCIAL SCIENCE / Death & Dying; Dead; Death -- Psychological aspects; Death -- Social aspects; Grief; Mourning customs